Failure mapping of adhesively bonded single lap joints : nondimensional analysis - Tang, J. H. (2014)
The debonding problem of single lap joints subjected to in-plane loading is analyzed based on nondimensional approach pioneered by Lai et al. (1996). This approach allows the determination of specific nondimensional energy release rate and prediction of debonding or adherend kinking mapping region. For equal moduli of adherend, the analysis reveals that asymmetrical configuration induces unfavorable conditions of higher debonding and kinking propensity. Compared to the experimental measurements, the analysis presented shows a fairly good agreement of expected failure mode for a given set of geometry and material parameters. The mapping of failure region from the nondimensional analysis is instructive as a design failure map for predicting the fracture behavior of asymmetrical single lap joints.